Association between Serum Hepcidin Levels and Insulin Resistance in Iraqi Type 2 Diabetes Patients - Oleiwi, Esraa Hasan; Hussein, Saba Zuhair (Iraqi Journal of Science, 2025)
The current study aimed to evaluate the impact of hepcidin levels on the diagnosis and management of T2DM patients and to investigate the association between their levels and insulin resistance. The study included 100 T2DM patients, which are divided into three groups according to disease duration: D1 (n=38; < 5 years), D2 (n=37; 5-10 years), D3 (n=25; >10 years), and 50 healthy persons as control (C). Fasting blood glucose (FBG) was determined by glucose oxidase-peroxidase and glycated haemoglobin A1c (HbA1c) by immunoturbidimetric assays. Serum insulin and hepcidin were evaluated using ELISA. Also, HOMA-IR and HOMA-β were calculated from FBG and insulin. The FBG, HbA1c, insulin, and HOMA-IR levels increased significantly, while HOMA-β and hepcidin levels decreased significantly in all patient groups compared to C. A significant difference in hepcidin levels was recorded between males and females in all groups. There was a significant negative correlation between HOMA-IR and hepcidin levels in all patient groups. Based on the results, it can be concluded that these biochemical markers are important in diagnosing and managing T2DM.